A large ectopic hepatocellular carcinoma with adrenal infiltration: a rare case report - Yang, Yongjun; Lu, Qiang; Li, Zonglin; Wang, Chen; Li, Yuanwei (Frontiers in Oncology, 2023)
Ectopic hepatocellular carcinoma (EHCC) originates from the ectopic liver, which refers to a liver organ or tissue unrelated to surrounding tissues. EHCC is a rare disease that lacks specific clinical signs, and preoperative diagnosis is often difficult. In a 61-year-old male patient with positive hepatitis B virus antibody, abdominal contrast-enhanced computed tomography scan showed a large heterogenously enhancing mass both on arterial and portal venous phase imaging arising from the right adrenal gland. Similar enhancement features were seen on magnetic resonance imaging. Serum potassium, aldosterone, cortisol, and plasma metanephrines were normal. The tumor markers of serum alpha-fetoprotein and alpha-fetoprotein-L3% were increased to 23.69 ng/mL and 82.1%, respectively. Exploratory laparotomy was performed and operative findings showed that the retroperitoneal tumor was disconnected from the right kidney and the liver, but invaded the right adrenal gland. Immunohistochemical examination showed that Arginase-1 was positive expression, and the retroperitoneal tumor was finally diagnosed as EHCC. We report a rare EHCC with adrenal infiltration that is difficult to diagnose preoperatively and mimics a retroperitoneal tumor or adrenal tumor, and we present a review of the literature on EHCC case reports.